Bacterial vaginosis as a risk factor of preterm premature rupture of membrane (PPROM) - Wiraguna, Aanak Agung Gde Putra; Rusyati, Luh Made Mas; Vijayamurthy, I Dewa Ayu Vanessa (Bali Dermatology and Venereology Journal, 2018)
Introduction: The pathogenesis of PPROM is complex and not fully understood. Recent studies showed that such role of genital tract infection as bacterial vaginosis in the pathogenesis of PPROM turned out to be present. They produce lipase enzymes in which they can form compounds with the fibrous tissue of amniotic membrane resulting in increased risk of rupture of the membrane.Objective This study aims to prove that bacterial vaginosis is a risk factor for preterm premature rupture of membrane.Material and methods: This research used case control method. Sampling was using the consecutive sampling method and had fulfilled inclusion and exclusion criteria with age-based matching, then vaginal swab sampling was conducted, painted with gram staining in the Dermalotogy and Venereology Laboratory of Sanglah Hospital, and Nugent score.Result: Total of 76 pregnant women with 24-36 weeks of gestation were investigated, 38 mothers with PPROM and 38 mothers with normal pregnancy. Average score of Nugent at preterm PROM was 7.18 and in normal pregnancy was 2.37. Bacterial vaginosis risking for PPROM 7 times (OR= 7.0, 95% CI= 1.21-17.68, p= 0.001).Conclusion: Bacterial vaginosis as a risk factor for the occurrence of PPROM.